EL ANÁLISIS FINANCIERO COMO UNA HERRAMIENTA PARA LA GESTIÓN FINANCIERA DE LAS PYME: Financial Analysis as A Tool For The Financial Management Of SMES - Murillo, Diego Alberto Alpuche; Hernández, Dra. Francisca Silva; Fernández, Dra. Candelaria Guzmán (IJRDO - Journal of Business Management, 2022)
Small and medium enterprises represent for Mexico a large part of the economic sustenance for millions of families nationwide, however, their life span is very short, it is estimated that the time that this type of companies lasts providing their products or services is 7 to 8 years, one of the great problems for which they fail to consolidate is due to their poor organization at the financial level. It is here that the analysis of financial reasons becomes very relevant for the proper management and maximization of resources of the organization. The purpose of this research is to make a descriptive study with documentary design that seeks to know the importance of financial reasons as an efficient financial management tool for SMEs, In conclusion, financial analysis is a fundamental tool for those small and medium-sized companies to achieve a management that can be profitable and achieve their objectives.